How fear emotion impacts collective motion in threat environment - Lü, Yi-Xuan; Zhang, Si-Ping; Meng, Guan-Yu; Guo, Bing-Hui; Liang, Xiao-Long; Wu, Zhi-Xi; Huang, Zi-Gang (Frontiers in Physics, 2024)
The emergence of collective behavior often depends on the adequate interaction of individuals through self-organization and the exchange of local information. When facing external threats, communication among individuals requires both rapid and effective information exchange to characterize sudden events. In this paper, we introduce the mechanism of emotions into the modeling of dynamics to study collective avoidance behavior in response to threats. A scenario involving a hidden dynamic threat is constructed to test the avoidance and survival capabilities of the collective when faced with a lack of effective information. By employing the activation and spread of emotion, the collective may self-organized and adeptly mitigate risks and enhance their own benefits. Through adjustments to the intensity of emotional activation, spread, and decay, rich behaviors emerge. Furthermore, relying on the regulation of fear and excitement, the collective exhibits different response strategies and action patterns when facing threats, in which the optimal performance from the macroscopic level is expectable.